Effectiveness and tolerability of methotrexate in pulmonary sarcoidosis: A single center real-world study - Fang, Chuling; Zhang, Qian; Wang, Na; Jing, Xiaoyan; Xu, Zuojun (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Pulmonary sarcoidosis patients who get disease progression despite corticosteroid treatment or can’t tolerate corticosteroid required second-line drug. Methotrexate (MTX) is the most widely used in our clinical practice. Data on its safety and efficacy at different doses are still limited, especially for those without folic acid supplements. Objective: To report effectiveness of different MTX dosages and tolerability of MTX in pulmonary sarcoidosis without folic acid supplements. Methods: A retrospective study on pulmonary sarcoidosis patients receiving MTX therapy with various dose ≥3 months was conducted. The primary outcome was change in high-resolution computed tomography (HRCT) before and after MTX therapy. Other efficacy parameters included SGRQ score, prednisone dose change, discontinuation and relapse-free survival. Response-linked factors and safety outcomes were also analyzed. Results: Overall, 49 patients (81.7%) were assessed as MTX responders by HRCT and there was no significant difference in clinical response rate among three groups with different doses. The health-related quality of life (HRQL) of the responders improved obviously, which was evidenced by SGRQ score declining from 16.7(IQR: 7.9-26.4) to 10.7(IQR: 4.8-19.3) (P=0.029). The corticosteroids sparing effect was confirmed in “responders” group (P<0.001). When MTX was discontinued in 11 responders with complete improvement, 2 patients experienced relapses within 15.5 (range: 1-30) months (mean follow-up time of these 11 responders: 13.5±13.0 months). No clinical characteristics were found related to MTX effectiveness. Adverse events occurred in 31.7% of the patients, with gastrointestinal-related being the commonest. Drug discontinuation owing to adverse events occupied 6.7% of the subjects. Conclusions: Nearly 80% of the sarcoidosis subjects had well response to MTX. Its effectiveness was irrelevant to the treatment dosages and baseline characteristics. A quite low relapse rate was witnessed in those complete responders discontinuing MTX therapies. The steroid-sparing effect, well drug tolerability and low drug withdrawal rate were observed in these patients even without folic acid supplements in clinical practice.